Criteria and indicators of the effectiveness of the methodological system of professional training of future grid automation engineers on the basis of causal training - Rudevich, N. (Problems of Engineer-Pedagogical Education, 2018)
In the article the system of criteria and indexes of the efficiency of the methodological system for vocational training of future grid automation engineers is worked out on the basis of the causal education. It is certain that the main efficiency criteria are the criteria of the level of development of project, operating, research and administrative competences. It is shown that the second hierarchical level in the system of criteria and indexes of efficiency of the methodological system for vocational training of future grid automation engineers, which is created on the basis of causal education, is represented by groups of indicators of the level of formation of professional knowledge and skills and groups of indicators of the level of formation of professionally relevant qualities for four types of activities. The groups of indicators of the level of formation of professional knowledge and skills for four types of activities must consist of indexes of knowledge acquisition and indexes of skills acquisition. The groups of indicators of the level of formation of professionally relevant qualities for four types of activities must consist of groups of indicators of the level of development of cognitive, motivational, emotionally-volitional, organizationallycommunicative qualities as well as universal ones which, in turn, will include the indicators of the level of formation of some separate qualities.